Drug delivery to the colon - Hua, Susan (Henry Stewart Talks, 2020)
Gastrointestinal drug delivery, Route for systemic drug delivery, Physiological and pharmaceutical considerations influencing drug delivery, Changes in gastrointestinal physiology in colonic diseases, Conventional and novel approaches to colon-specific drug delivery, Translational development aspects of novel formulations